2017
DOI: 10.1002/ldr.2846
|View full text |Cite
|
Sign up to set email alerts
|

Pyrolysis temperature during biochar production alters its subsequent utilization by microorganisms in an acid arable soil

Abstract: Biochar amendment of agricultural soils can have a significant impact on microbial carbon (C) metabolism by providing C substrates and altering soil properties, including amelioration of soil acidity. It remains unclear whether available C of biochar or its pH effects determines the utilization of biochar by microorganisms. Compound‐specific stable 13C isotope analysis of phospholipid fatty acids (13C‐phospholipid fatty acid analysis) was used to explore which microbial group utilized biochar distinguished wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 32 publications
0
35
2
Order By: Relevance
“…A biochar-treated acid soil was evaluated for soil microbial communities by PLFA; where increased PLFA was observed compared to the control soil after 431 days of incubation (Luo et al 2018). It has been demonstrated that higher surface area of biochar could adsorb water, nutrients, and soluble C which in turn facilitate the microbial colonization (Luo et al 2018). Moreover, the PLFA revealed that Gram-positive bacteria used biochar C as substrate from the biochar produced at 350 °C than that at 700 °C.…”
Section: Soil Microbial Community Structurementioning
confidence: 99%
“…A biochar-treated acid soil was evaluated for soil microbial communities by PLFA; where increased PLFA was observed compared to the control soil after 431 days of incubation (Luo et al 2018). It has been demonstrated that higher surface area of biochar could adsorb water, nutrients, and soluble C which in turn facilitate the microbial colonization (Luo et al 2018). Moreover, the PLFA revealed that Gram-positive bacteria used biochar C as substrate from the biochar produced at 350 °C than that at 700 °C.…”
Section: Soil Microbial Community Structurementioning
confidence: 99%
“…Biochar amendment influences microbial community and functioning not only by providing available organics but also indirectly by decreasing soil acidity by cations in ash. Compound‐specific 13 C analysis of phospholipid fatty acids ( 13 C‐PLFA) was used to determine which microbial group utilized C added with biochar (Luo et al, ). C4 Miscanthus biochar (δ 13 C = −12.2‰), prepared at 350 and 700 °C, was applied to a highly acidic soil (pH 3.7, δ 13 C = −27.7‰) from Rothamsted Research Station and incubated for 14 months.…”
Section: Overview Of the Papers In The Special Issuementioning
confidence: 99%
“…The 13 C‐PLFA showed that all microbial groups, and especially G+ bacteria, used the C from the biochar350, but not from the biochar700. In conclusion, biochar utilization by microorganisms is largely determined by the pyrolysis temperature controlling the C availability and not by the pH effects (Luo et al, ).…”
Section: Overview Of the Papers In The Special Issuementioning
confidence: 99%
See 2 more Smart Citations